Development & application of a wearable non-differential calorimeter for skin heat transfer analysis - Pedro Jesús Rodríguez de Rivera; Miriam Rodríguez de Rivera; Fabiola Socorro; Manuel Rodríguez de Rivera (PLoS ONE, 2025)
The thermal properties of human skin are of great interest for understanding local and global body heat loss, various physiological responses or even skin injuries. This study presents a wearable, non-invasive skin calorimeter designed for in vivo measurement of skin heat flux, heat capacity, and thermal resistance. The device, based on the principle of non-differential heat conduction calorimetry, consists of a programmable thermostat, a heat flux sensor and a Peltier cooling system. To operate the device, we propose and calibrate a calorimetric thermal model that includes the skin. This new model approach allows to estimate the core temperature of the tissue where the measurement is performed. Experimental validation of the device was carried out on localized skin areas, both at rest and during moderate physical activity. This skin calorimeter allows determination of thermal properties in different skin regions, with an accuracy of ± 2 mW for the heat flux, ± 1 K/W for the thermal resistance, and ± 0.05 J/K for the heat capacity, for a 2 × 2 cm² skin region. The results confirm the applicability of these devices in sports medicine, thermoregulation studies, and medical diagnostics. This work also includes simulations of the calorimeter’s operation, which help to define its operating range and to study the interaction between the device and the human skin.